The Dickens boy [large type] - Keneally, Thomas (Thorndike Press large print basic, 2022)
"Edward Dickens, the tenth child of England's most famous author Charles Dickens, has consistently let down his parents. Unable to apply himself at school and adrift in life, the teenaged boy is sent to Australia in the hopes that he can make something of himself--or at least fail out of the public eye. He soon finds himself in the remote Outback, surrounded by Aboriginals, colonials, ex-convicts, ex-soldiers, and very few women. Even on the other side of the world, Edward encounters the same rabid veneration of his father that exists in England. But Edward has a secret: he has never read a single word of his father's beloved writing. Determined to prove to his parents and more importantly, himself, that he can succeed in this vast and unfamiliar wilderness, Edward works hard at his new life amidst various livestock, bushrangers, shifty stock agents, and frontier battles. By reimagining the tale of a fascinating yet little-known figure in history, this rollicking, high-spirited tale offers penetrating insights into Colonialism and the fate of Australia's indigenous people, and a wonderfully intimate portrait of Charles Dickens, as seen through the eye of his exiled son."--